Quasi-harmonic analysis of fortnightly suspended sediment response to semi-diurnal tidal currents - Zhu, Zichen; Liang, Bingchen; Chen, Bin; Yang, Bo; Chi, Wanqing; Xu, Hao; Hu, Zejian (Frontiers in Marine Science, 2024)
Suspended sediment concentration (SSC) is an important consideration in marine engineering.Sediment movement characteristics can be studied by considering the fortnightly behaviour of SSC. However, this consideration currently lacks accurate mathematical representation. In this study, a computationally efficient mathematical model capable of providing analytical solutions for predicting SSC based on resuspension, deposition, and advection was developed to further investigate the mathematical interpretation of fortnightly SSC behavior in coastal areas dominated by M 2 , S 2 , O 1 , K 1 , M 4 , and MS 4 tides. The model decomposed the SSC into 35 quasi-harmonic terms, as well as two terms with a fortnightly period. The model was applied at five observation sites in the Bohai Sea, Yellow Sea and East China Sea, China, and validated to be able to reproduce the fortnightly variation of SSC. The results show that the primary fortnightly SSC term was generated by the combined action of M 2 and S 2 tidal currents and had a tidal frequency of 1.0159 • h -1 , which was equal to the difference between the frequencies of the two partial tides. The amplitude of the fortnightly term was influenced by the M 2 and S 2 tidal currents, the resuspension and deposition properties of the sediment, and the mean water depth. The resuspension properties only affected the amplitude of the fortnightly SSC term but did not affect the phase. The deposition properties affected both amplitude and phase. The quasi-harmonic analysis indicates that in certain shallow sea areas with strong nonlinear tidal interactions, the amplitude of the M 4 tidal elevation influences the mean SSC, while the amplitude of the MS 4 tidal elevation affects the fortnightly SSC amplitude. As the simplified model is based on certain assumptions, the application conditions of the quasi-harmonic analytical solution include an approximate reciprocating flow pattern, a tidal range significantly smaller than the water depth.Our results provide a mathematical solution for the fortnightly evolution of suspended sediment.